Pelatihan Teknik Dasar Taekwondo untuk Meningkatkan Motorik dan Percaya Diri Siswa SDN Inpres 127 Moncongloe - Rerung, Charmila Tandi; Aulria, Siti Nurhalizah Mutia; Arga, Arga; Rahmi, Rahmi; Suwardi, Suwardi; Hudain, Muh. Adnan; Mappaompo, M. Adam (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This community service program aims to enhance the motor skills and self-confidence of students at SDN Inpres 127 Moncongloethrough basic Taekwondo training. The program was conducted over 12 weeks, involving 40 students from grades IV and V. The implementation method included three stages: preparation involving coordination with the school and training module development; execution consisting of pretests, training, and posttests; and evaluation and follow-up. The results indicated significant improvements in students' motor skills in locomotor aspects and object control, as well as increased self-confidence in facing challenges and social interactions. The success of this program suggests that basic Taekwondo training can be an effective alternative for physical and psychological development in elementary students. Sustainability can be achieved by establishing a Taekwondo club at the school and providing training for physical education teachers.